The Evaluation of Senior High School Geography Curriculum using Countenance’s Model and A Responsive Approach - Saptorini, Peni; A. Ghani, Abd. Rahman; Binfas, Maman Abdul Majid (Jurnal Pendidikan Geografi Gea, 2021)
This study aims to evaluate the Geography curriculum for senior high school using Countenance’s model and responsive approach. This study is qualitative research and it used the interview and document study for data collecting. The interview was done by interviewing 15 Geography teachers of senior high school in the West Java Province. The interview also has been done by interviewing the leader of Association of Indonesian Geography and the Coordinator of Facilitation and Curriculum Evaluation from the Center of Curriculum of Ministry of Education and Culture. Document study has been done by studying the document of 2018 Revision from 2013 Curriculum. The data of the research has been analyzed using interactive analysis from Miles and Huberman. The results shows: (1) 75% interviewees said that the design of Geography curriculum should be reviewed; (2) 87% interviewees said that having Geography in the specialization social subject is less precise;(3)  63% interviewees said that distribution of basic competency and material of Geography for class X-XII should be reorganized;(4) Need improvement in Geography learning, so it would encourage critical and analytical thinking, also the student’s geocapabilities. The recommendations are: (1) The team of curriculum development should consider the suggestions  about the change of Geography curriculum; (2) MGMP Geography in the regencies or provinces should arrange any programs to increase the competencies of Geography teachers which is collaborated with the other stakeholders; (3) Formulating the draft of new curriculum should consider any suggestions so Geography would be given the realistic contribution in lives.